2022
DOI: 10.1212/wnl.0000000000200989
|View full text |Cite
|
Sign up to set email alerts
|

Association of Enlarged Perivascular Spaces With Amyloid Burden and Cognitive Decline in Alzheimer Disease Continuum

Abstract: Background and Objectives:To investigate the effects of enlarged perivascular space (EPVS) on amyloid burden and cognitive function in Alzheimer’s disease (AD) continuum.Methods:We retrospectively reviewed 208 patients with AD across the cognitive continuum (preclinical, prodromal, and AD dementia) who showed amyloid deposition on 18F-florbetaben positron emission tomography scans and 82 healthy controls. EPVSs were counted for each patient in the basal ganglia (BG), centrum semiovale (CSO), and hippocampus (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In fact, it has been suggested by DTI-ALPS (diffusion tensor image analysis along the perivascular space), an MRI-based approach ( Taoka et al, 2017 ), that CAA is indeed associated with lower MVPVS diffusivity ( Xu et al, 2022 ). However, by employing 11C-Pittsburgh B compound (PIB) PET ( Banerjee et al, 2017 ) or florbetaben/florbetapir PET ( Sepehrband et al, 2021 ; Wang et al, 2021 ; Jeong et al, 2022 ), the association between MVPVS and CAA has not been confirmed in the Alzheimer’s disease continuum, which commonly co-occurs with cerebral amyloid angiopathy. In addition, two studies found an association of MVPVS with tau by employing flortaucipir PET ( Sepehrband et al, 2021 ; Wang et al, 2021 ) or CSF analysis ( Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been suggested by DTI-ALPS (diffusion tensor image analysis along the perivascular space), an MRI-based approach ( Taoka et al, 2017 ), that CAA is indeed associated with lower MVPVS diffusivity ( Xu et al, 2022 ). However, by employing 11C-Pittsburgh B compound (PIB) PET ( Banerjee et al, 2017 ) or florbetaben/florbetapir PET ( Sepehrband et al, 2021 ; Wang et al, 2021 ; Jeong et al, 2022 ), the association between MVPVS and CAA has not been confirmed in the Alzheimer’s disease continuum, which commonly co-occurs with cerebral amyloid angiopathy. In addition, two studies found an association of MVPVS with tau by employing flortaucipir PET ( Sepehrband et al, 2021 ; Wang et al, 2021 ) or CSF analysis ( Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is illustrated by studies, described in detail above, investigating ePVS in patients with focal epilepsy that indicate that PVS asymmetry is correlated to the SOZ. 62,66,67 As in generalized epilepsy and neurodegenerative and neuroinflammatory diseases, 28,29,31,32,49,103 it is thus hypothesized that in PSE and other focal epilepsy conditions, it is relative ePVS asymmetry rather than absolute ePVS number and volume, which is associated with pathology and epileptogenesis. 62,66,67 3.…”
Section: F I G U R Ementioning
confidence: 99%
“…103,106 While ePVS may have limited use in the differential diagnosis of dementias, studies in AD have shown relationships with cognitive decline and studies in MS associations with disease severity. 29,31 Therefore, ePVS may be a marker of disease severity and sequelae.…”
Section: With the Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the aforementioned evidence and deductions are compelling, some studies did not find clear associations of AD diagnosis or pathology with PVS burden (30,31), casting doubt on the involvement of PVS alterations in AD and the validity of the clearance hypothesis. Longitudinal studies that could establish specific factors that mechanistically drive PVS enlargement are scarce due to the persistent methodological challenges to quantify PVS reliably and computationally using repeated measures (32).…”
Section: Introductionmentioning
confidence: 99%